Contribution Analysis of Assembled Brake System to Reduce Squealing - Seong-Jin Kwon; Chan-Jung Kim (Applied Sciences, 2022)
Brake noise is a problem that is still being studied owing to continuous issues in the vehicle industry, and many countermeasures have been suggested using experimental and simulation approaches. The assembled brake system comprises several subparts, and a contribution analysis is an efficient solution for selecting the subpart with the most influence on squealing. In this study, a finite-element model of the assembled brake system was verified with modal test results for each part. Then, a forced response analysis of the assembled brake system model was conducted to obtain the spectral response vector of the subparts under white-noise excitation. A contribution analysis was formulated by calculating the similarity between the total and partial response vectors of each part and deriving the contribution index of all subparts of interest. The brake pad was selected as the target of design modification, and the feasibility was validated using an experimental chassis dynamometer test.